2022
DOI: 10.2306/scienceasia1513-1874.2022.010
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical changes in shoot and root organs of common vetch (Vicia sativa L.) after exposure to drought stress

Abstract: Morphological and biochemical responses of shoot and root organs of post-drought stress vetch plant were investigated. Vetch seedlings were exposed to drought stress (100 g/l PEG 6000 ) under in vitro conditions. Parameters were measured on 14-day-old seedlings. Under drought stress, shoot and root length, fresh weight, and water content were decreased. The dry matter ratio (DMR) increased in both the root and the shoot, and an increase in root dry weight was detected. Moreover, drought induced changes in acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
(47 reference statements)
2
3
0
Order By: Relevance
“…Therefore, it can be seen as an adaptation developed by this plant so that it can withstand the stress factor more strongly. These findings support earlier research by Hamidi and Safarnejad (2010), Demiroğlu-Topçu and Özkan (2016), Beyaz (2022) and Ahmed et al, (2022) who found significant decreases in growth paramaters of alfalfa, sainfoin, common vetch and sesame under PEG6000 induced drought stress. The partitioning of dry matter (DM) in plants is closely correlated with crop productivity during drought stress (Rauf and Sadaqat, 2007).…”
Section: Figure 2 the Effect Of Different Levels (0% Peg6000 4% Peg60...supporting
confidence: 92%
See 2 more Smart Citations
“…Therefore, it can be seen as an adaptation developed by this plant so that it can withstand the stress factor more strongly. These findings support earlier research by Hamidi and Safarnejad (2010), Demiroğlu-Topçu and Özkan (2016), Beyaz (2022) and Ahmed et al, (2022) who found significant decreases in growth paramaters of alfalfa, sainfoin, common vetch and sesame under PEG6000 induced drought stress. The partitioning of dry matter (DM) in plants is closely correlated with crop productivity during drought stress (Rauf and Sadaqat, 2007).…”
Section: Figure 2 the Effect Of Different Levels (0% Peg6000 4% Peg60...supporting
confidence: 92%
“…However, this increase is indicated by root shoot dry matter ratio (Figure 2I). Similar to the research findings, Beyaz (2022) reported that in vitro PEG6000 drought treatment (10%) caused an increase in dry matter ratio in both shoot and root organs of common vetch, and this increase was more in the root. A decrease in water content and disruption to cellular membranes, which aid the body in coping with abiotic stresses such as drought, are the primary impacts of stress (Zhou et al, 2012).…”
Section: Figure 2 the Effect Of Different Levels (0% Peg6000 4% Peg60...supporting
confidence: 88%
See 1 more Smart Citation
“…Another study found that drought stress increased the activity of antioxidant enzymes in both shoot and root tissues, implying that the antioxidant defense system plays a role in removing reactive oxygen species. The author also reported that watering the plants after drought stress partially restored their morphological and biochemical characteristics, indicating some degree of recovery from drought damage [65]. SRPP4, which belongs to a stressrelated protein category [66], was overexpressed under severe drought.…”
Section: Plos Onementioning
confidence: 93%
“…In general, the plants in response to drought stress cause changes in several important markers, including malondialdehyde (MDA), proline, and the activity of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) ( Beyaz, 2019 ; Beyaz, 2022 ). These markers are often used as the basis for drought stress studies of pepper ( Kim et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%